Action Machines - Towards a Framework for Model Composition, Exploration and Conformance Testing Based on Symbolic Computation - Tillmann, Nikolai; Schulte, Wolfram; Veanes, Margus (Quality Software, 2005. (QSIC 2005). Fifth International Conference on, 2005)
We report on a framework for model composition, exploration, and conformance testing based on symbolic execution. The foundations of this framework are given by so-called action machines, a variation of labeled transition systems which communicate over synchronously stepped actions and constraints attached to them. The implementation is based on XRT, an exploration engine for .NET CIL code which supports symbolic computation. The main application is in the area of model-based conformance testing, where our approach addresses practical problems users at Microsoft have in applying model-based testing technology.